Effect of oregano (Origanum vulgare L. ssp. hirtum) and clove (Eugenia spp.) nanoemulsions on Zygosaccharomyces bailii survival in salad dressings. (15th October 2019) - Ribes, Susana; Fuentes, Ana; Barat, Jose Manuel
Highlights: Oregano and clove nanoemulsions were used as antifungals in media and dressings. The effect of nanoemulsions on the sensory profile of dressings was tested. Efficacy of essential oil nanoemulsions against Z. bailii was demonstrated. Addition of nanoemulsions to salad dressings prolonged their shelf life. Sensory panellists accepted the salad dressing with oregano nanoemulsion. Abstract: This work aimed to evaluate the in vitro effect of encapsulated oregano and clove essential oils on oil-in-water nanoemulsions against Zygosaccharomyces bailii. The antifungal efficacy of these nanoemulsions and their sensory acceptance were tested in salad dressings . Both essential oils were effective inhibitors against the target yeast, with minimal inhibitory and fungicidal concentrations of 1.75 mg/mL. In the in vitro assay done with the nanoemulsions, no yeast growth was observed for any tested essential oil concentration. In the salad dressings, all the formulations were able to reduce Z. bailii growth compared to the control, and only those samples with 1.95 mg/g of essential oil were capable of inhibiting yeast development after 4 inoculation days. The sensory acceptance of the dressing containing the nanoemulsions was similar to the control dressing in appearance, consistency and colour terms. These results evidence the antifungal activity of oregano and clove nanoemulsions against Z. bailii .